Role of Titin Missense Variants in Dilated Cardiomyopathy - Begay, Rene L. (J Am Heart Assoc, 2015)
BACKGROUND: The titin gene (TTN) encodes the largest human protein, which plays a central role in sarcomere organization and passive myocyte stiffness. TTN truncating mutations cause dilated cardiomyopathy (DCM); however, the role of TTN missense variants in DCM has been difficult to elucidate because of the presence of background TTN variation. METHODS AND RESULTS: A cohort of 147 DCM index subjects underwent DNA sequencing for 313 TTN exons covering the N2B and N2BA cardiac isoforms of TTN. Of the 348 missense variants, we identified 44 “severe” rare variants by using a bioinformatic filtering process in 37 probands. Of these, 5 probands were double heterozygotes (additional variant in another DCM gene) and 7 were compound heterozygotes (2 TTN “severe” variants). Segregation analysis allowed the classification of the “severe” variants into 5 “likely” (cosegregating), 5 “unlikely” (noncosegregating), and 34 “possibly” (where family structure precluded segregation analysis) disease‐causing variants. Patients with DCM carrying “likely” or “possibly” pathogenic TTN “severe” variants did not show a different outcome compared with “unlikely” and noncarriers of a “severe” TTN variant. However, the “likely” and “possibly” disease‐causing variants were overrepresented in the C‐zone of the A‐band region of the sarcomere. CONCLUSIONS: TTN missense variants are common and present a challenge for bioinformatic classification, especially when informative families are not available. Although DCM patients carrying bioinformatically “severe” TTN variants do not appear to have a worse clinical course than noncarriers, the nonrandom distribution of “likely” and “possibly” disease‐causing variants suggests a potential biological role for some TTN missense variants.